Electrophysiology in neuropathic pain: a bibliometric analysis and literature review - Yidan Cui; Chen Lv; Wenjian Yan; Lidan Zhang; Ning Sun; Xin Zhang; Zhen Zhong (Frontiers in Neuroscience)
ObjectiveNeuropathic pain (NP), a prevalent chronic condition with increasing global incidence, mainly relies on electrophysiology (EP) to decode its mechanisms. However, existing research lacks systematic integration, failing to track hotspots and frontiers effectively. In this study, we used bibliometric analysis and systematic review to clarify technological breakthrough directions and facilitate the development of electrophysiological phenotype-based precision diagnostics.MethodsLiterature was retrieved from the Web of Science Core Collection (WoSCC). A total of 2,234 reviews and articles were obtained from 2005 to 2024. Statistics and visualization analysis were performed using Bibliometrix (R), VOSviewer, CiteSpace, and Microsoft Excel 2024.ResultsPublications and citations in this field are rising. The USA leads in publications (613, 27.44%) and academic impact (H-index = 96). China’s academic impact remains behind when compared to other countries. North American and Western European institutions form robust collaboration networks, whereas Asian institutions exhibit weaker regional partnerships. Authors with high production, such as Khanna, Rajesh and Waxman, Stephen G, and highly cited authors such as Woolf, CJ play a key leading role in the development of the field. Journals like Pain and Journal of Neuroscience are the cardinal dissemination mediums. Keyword analysis reveals research hotspot expands from the basic structure of “dorsal root ganglion” and” sensory neuron” to pain-related dynamic changes and disease prevalence characteristics. “Plasticity” and “connectivity” signaled a shift in research toward network mechanisms and precise interventions. “Woolf CJ, 2011” and “Dib-Hajj SD, 2010” have high citation and co-citation frequencies. The emergence of new directions such as “dynamic pain connectome” and “computational modeling research” reflects the trend of multidisciplinary integration.ConclusionFor the first time, we have constructed a complete lineage from basic research to clinical translation in this field, confirming the key role of EP technology in analyzing the mechanism of nociceptive sensitization, neuroplasticity, and neural network connectivity reconfiguration, which provides a basis for developing precise diagnostic and therapeutic solutions based on electrophysiological phenotypes. Future research should focus on technology standardization, cross-institutional data sharing, clinical translation, and connectomics-oriented individualized analgesic strategies to promote NP diagnosis and treatment toward precision, dynamics, and systematization.